Multivariate and long-term time series analysis to assess the effect of nitrogen management policy on groundwater quality in Wallonia, BE - E. Verstraeten; A. Alonso; L. Collier; M. Vanclooster (Hydrology and Earth System Sciences)
Groundwater nitrate contamination remains a significant environmental and health concern, as the effectiveness of nitrogen management programmes has shown mixed results. This study leverages nearly 2 decades of groundwater monitoring data to assess and explain nitrate contamination trends in vulnerable zones in Wallonia, Belgium, following the implementation of the regional sustainable nitrogen management programme.